Strategies of controlling vibriosis in fish - Huzmi, Hasnazifa; Md Yasin, Ina Salwany; Mohd Ikhsan, Natrah Fatin; Ismail, Fadhil Syukril; Abd Karim, Murni Marlina (Science Alert, 2019)
The growth of the aquaculture industry is becoming more important in the food production sector. Presently, the biggest problem in aquaculture is bacterial diseases that infect the host thus causing outbreaks and economic losses. Vibriosis is a potentially lethal threat in commercial fish farming. Based on previous researches, various infections of the Vibrio genus have been reported hence their virulence is not fully understood. This review aims to provide enlightenment through research findings on Vibriosis-infected fish. Besides, some guidelines regarding control measures of Vibrio in aquaculture, such as the application of immunostimulant, antibiotics, probiotics and quorum sensing molecules, will be also reviewed.